2022
DOI: 10.1093/jisesa/ieac066
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Fungal Diversity and Abundance in the Black Soldier Fly and its Environment

Abstract: Detritivorous insects that flourish in decaying environments encounter microorganisms throughout their life cycle. However, it is not clear whether the microbial composition of the decaying environment affects the microbial composition of the insect gut, or whether the opposite is true, with the microorganisms that are adapted to the insect’s digestive system being dispersed by the insects to new habitats, thereby becoming more and more common in the environment. To test these questions the fungal composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It can be observed that the moulds were distributed at higher concentrations in frass than in larvae and feed. It has been reported that BSFL gut is characterized with a diverse set of fungal communities including Candida , Dipodascaceae , Trichosporon , Pichia , species where their occurrence depends upon the substrate used for rearing the larvae [ 42 , 43 , 44 ]. Recent studies have also reported the passage of different genera of bacteria present in the guts of BSFL through their digestive tracts as consequence of the digestion of different waste streams or feeds used to grow the larvae [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that the moulds were distributed at higher concentrations in frass than in larvae and feed. It has been reported that BSFL gut is characterized with a diverse set of fungal communities including Candida , Dipodascaceae , Trichosporon , Pichia , species where their occurrence depends upon the substrate used for rearing the larvae [ 42 , 43 , 44 ]. Recent studies have also reported the passage of different genera of bacteria present in the guts of BSFL through their digestive tracts as consequence of the digestion of different waste streams or feeds used to grow the larvae [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…These studies reveal that H. illucens can host a wide variety of fungi, mainly belonging to the phylum Ascomycota and including, among others, the genera Pichia, Candida, Diutina, Kluyveromyces, Trichosporon and Fusarium. Several of these studies have shown that the fungal microbiota profiles in H. illucens is largely influenced by the nature of the substrate [50,59,66,75]. For example, plant waste tends to be associated with a greater diversity of fungal species compared to chicken feed [59].…”
Section: Beyond the Bacterial Dimension: The Mycobiota And The Virobiotamentioning
confidence: 99%